Pengaruh Struktur Modal, Ukuran Perusahaan, dan Likuiditas Terhadap Tingkat Pengembalian Aset PT United Tractors TBK - Lubis, Fitrah Maulidiyah (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This research was conducted with the aim of measuring how internal factors such as Capital Structure, Firm Size, and Liquidity contribute to influencing the return on assets (ROA) of PT United Tractors Tbk. The research method used is a descriptive quantitative method. This study utilizes secondary data directly sourced from the annual financial statements of PT United Tractors Tbk, journals, and other literature relevant to the research topic. Data analysis was performed using SPSS software by measuring the financial ratios of the Debt to Equity Ratio, total assets, and Current Assets. The conclusion of this study states that capital structure, firm size, and liquidity do not contribute to influencing the return on assets of PT United Tractors Tbk